Integrasi Pembelajaran Emosional dan Prinsip Neuroedukasi untuk Menguatkan Empati dan Pengembangan Karakter pada Siswa Sekolah Dasar - Kholis, Nur; Indriharta, Lilik; Sholeh, Makherus; Remanita, Yuan; Binti Salamah, Anis (Muallimun : Jurnal Kajian Pendidikan dan Keguruan, 2025)
Learning in elementary schools remains predominantly focused on cognitive aspects, leaving the emotional dimensions that significantly influence students' empathy and character development unmanaged as an integral part of the learning process. As a result, issues such as low social sensitivity, limited learning engagement, and weakened intrinsic motivation persist. This study employs a qualitative method with a phenomenological approach, involving eight students, three teachers, and the school leader as research subjects. The study focuses on the emotional learning experiences of students and the neuroeducational practices of teachers. The research was conducted at SDI Ibadurrahman Blitar. Data were collected through in-depth interviews, classroom observations, and documentation. Data validity was ensured through source triangulation, technique triangulation, member checking, and bracketing. Data analysis was conducted through horizontalization, which involved reducing and developing essential themes. This study aims to analyze how students' emotional experiences during learning contribute to the formation of empathy and character, as well as how teachers understand and apply neuroeducational principles to create a learning environment that supports such development. The findings show that a favorable emotional climate, collaborative learning, routine reflection, and teacher role modeling are effective in activating emotional regulation, increasing learning motivation, fostering empathy, and shaping students' prosocial character.